Influence of the Covid-19 Pandemic on the Development of the Railway Transport in Bulgaria (Научни трудове на УНСС, 2023)
The freight railway transport has got an important role in the national transport system, carrying out the movement of goods on medium length and long distances, where the passenger railway transport not only fulfils the purely commercial transportation side but it also has a social function supplying to the population access to social transportation services. In the current research is analysed the development of the freight and passenger railway carriage in Bulgaria for the period of 2011 – 2020. The period reviewed starts with the years of recovery of the economy of the country from the worldwide financial-economic crisis and ends with the entering into the crisis caused by the Covid-19 pandemic. The main goal of the study is to follow the trends of the development of the freight and passenger railway transport and to determine how the occurrence of the Covid-19 pandemic affected the railway transportation activities.